GLI1-Rearranged Enteric Tumors: Updates on Clinicopathologic and Molecular Genetics Features - Ahmed I. Younes; Haider A. Mejbel (Cells)
Recent advances in molecular genetics, particularly in identifying and characterizing genetic abnormalities within mesenchymal neoplasms, have led to a more comprehensive and evolving classification system. Modern technological developments in cytogenetics and next-generation sequencing have enabled the analysis of small clinical samples, expanded our understanding of tumor biology, and improved the diagnostic, prognostic, and predictive precision by identifying targeted genetic alterations, confirming the presence of fusion transcripts, and/or revealing the overexpression of specific genes and their targets. In this review, we focus specifically on the GLI1-rearranged enteric tumor, a recent clinicopathological entity that has emerged within the expanding classification of mesenchymal tumors. Herein, we aim to explore the histopathological features, molecular genetic characteristics, and clinical outcomes in these tumors. Due to their rarity and the extensive overlapping in their histopathological and molecular features with other neoplasms, continued research and systematic documentation of GLI1-rearranged enteric tumors is necessary to better understand their biological behavior, develop more accurate prognostic indicators, and establish optimal treatment strategies.